Titrating Tipsy Targets: The Neurobiology of Low-Dose Alcohol. (June 2017) - Cui, Changhai; Koob, George F.
Abstract : Limited attention has been given to our understanding of how the brain responds to low-dose alcohol (ethanol) and what molecular and cellular targets mediate these effects. Even at concentrations lower than 10 mM (0.046 g% blood alcohol concentration, BAC), below the legal driving limit in the USA (BAC 0.08 g%), alcohol impacts brain function and behavior. Understanding what molecular and cellular targets mediate the initial effects of alcohol and subsequent neuroplasticity could provide a better understanding of vulnerability or resilience to developing alcohol use disorders. We review here what is known about the neurobiology of low-dose alcohol, provide insights into potential molecular targets, and discuss future directions and challenges in further defining targets of low-dose alcohol at the molecular, cellular, and circuitry levels. Trends: Low doses of alcohol at concentrations that can be achieved by social drinking (1–3 drinks) impact brain function and behavior. Low-dose alcohol impacts neuronal activity and synaptic function; however, there is a lack of understanding precisely what molecular targets mediate such effects and what brain neurocircuits respond to low-dose alcohol. Alcohol allosterically modulates a variety of receptors, channels, and signaling molecules with a wide range of sensitivities. Understanding what molecular and cellular targets mediate the initial effects of alcohol will provide a window into the early stages of neuroplasticity that contribute to vulnerability and resilience to developing alcohol use disorders.